2019
DOI: 10.1186/s12916-019-1355-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between diabetes and risk of cardiovascular disease, cancer, and all-cause and cause-specific mortality: a systematic review and meta-analysis of 5,162,654 participants

Abstract: Background Studies have suggested sex differences in the mortality rate associated with diabetes. We conducted a meta-analysis to estimate the relative effect of diabetes on the risk of all-cause, cancer, cardiovascular disease (CVD), infectious disease, and respiratory disease mortality in women compared with men. Methods Studies published from their inception to April 1, 2018, identified through a systematic search of PubMed and EMBASE and review of references. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 96 publications
(52 reference statements)
7
98
1
1
Order By: Relevance
“…Besides, the risk of chronic diseases also increased both in men and women when BMI was in the "normal" range (18.5-24 kg/m 2 ), and a sharp increase was observed when BMI was in the range of 21.08-21.97 kg/m 2 in women or 22.59-23.89 kg/m 2 in men. Previous studies have shown that women have a higher risk of chronic diseases such as cardiovascular disease and diabetes than men (14,27). In the present study, it is further found that the risk of diseases in women is significantly higher than men at the same BMI level, and the differences gradually increase when BMI is >25 kg/m 2 , which was consistent with previous study (28).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, the risk of chronic diseases also increased both in men and women when BMI was in the "normal" range (18.5-24 kg/m 2 ), and a sharp increase was observed when BMI was in the range of 21.08-21.97 kg/m 2 in women or 22.59-23.89 kg/m 2 in men. Previous studies have shown that women have a higher risk of chronic diseases such as cardiovascular disease and diabetes than men (14,27). In the present study, it is further found that the risk of diseases in women is significantly higher than men at the same BMI level, and the differences gradually increase when BMI is >25 kg/m 2 , which was consistent with previous study (28).…”
Section: Discussionsupporting
confidence: 92%
“…However, the existence of sex differences seems to be ignored when studying the association between obesity and chronic diseases. For example, a systematic review found that women with diabetes had a significantly higher risk of coronary heart disease, cardiovascular disease (CVD) mortality and all-cause mortality than men (14). Considering the sex differences (15), the health risks of the population cannot be adequately predicted by dividing the population into 4 categories: underweight, normal, overweight and obesity (16).…”
Section: Introductionmentioning
confidence: 99%
“…As in our study, a meta-analysis that looked into sex differences in the association between diabetes and risk of CVD, cancer, and mortality of 49 prospective studies found that women had a 13% greater risk of all-cause mortality associated with diabetes, and there was a 30% significantly greater excess risk of CVD mortality in women with diabetes compared to men [25]. Interestingly, a study from Taiwan found that among patients with coronary artery disease, the impact of T2DM on mortality was consistently higher in women than in men, but the differences across sexes were not statistically significant after 1996, that is, after the wide application of coronary stents for CVD treatment [26].…”
Section: Discussionsupporting
confidence: 68%
“…It is well established that individuals who experience short sleep duration and poor sleep quality have a higher risk of obesity, glucose intolerance, insulin resistance and poor glycaemic control, which would directly and indirectly affect outcomes among those with diabetes [19]. Moreover, studies have suggested that sex difference in the mortality rate associated with diabetes and age at onset of type 2 diabetes is a prognostically important determinant for survival outcomes [20,21]. The role of sleep in this association remains unclear; although, it is biologically plausible that too little or too much sleep in people with type 2 diabetes would lead to poorer survival outcomes.…”
Section: Introductionmentioning
confidence: 99%